2021
DOI: 10.1101/2021.09.08.459417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-Dimensional Gene Expression and Morphology Profiles of Cells across 28,000 Genetic and Chemical Perturbations

Abstract: Populations of cells can be perturbed by various chemical and genetic treatments and the impact on the cells gene expression (transcription, i.e. mRNA levels) and morphology (in an image-based assay) can be measured in high dimensions. The patterns observed in this profile data can be used for more than a dozen applications in drug discovery and basic biology research, but both types of profiles are rarely available for large-scale experiments. We provide a collection of four datasets with both gene expression… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…A recent patch-seq study in the adult mouse motor cortex supports a lack of discrete boundaries in the adult mouse primary motor cortex, providing evidence of a continuum of correlated transcriptomic and morphoelectrical clusters present within families of cells (Scala et al, 2020). Consistent with these observations, recent comprehensive work has shown that while gene expression can be correlated to a cell's electrophysiology and morphology, each additional parameter adds slightly more nuanced variation (Nandi et al, 2020;Haghighi et al, 2021). As tools emerge to interrogate individual cell connectivity and merge them with neuronal subtypes defined in other contexts, heterogeneity has been identified within "subclasses" (Campagnola et al, 2021).…”
Section: Bridging Molecular and Functional Characterization Of Areas With Multi-omic Analysesmentioning
confidence: 77%
“…A recent patch-seq study in the adult mouse motor cortex supports a lack of discrete boundaries in the adult mouse primary motor cortex, providing evidence of a continuum of correlated transcriptomic and morphoelectrical clusters present within families of cells (Scala et al, 2020). Consistent with these observations, recent comprehensive work has shown that while gene expression can be correlated to a cell's electrophysiology and morphology, each additional parameter adds slightly more nuanced variation (Nandi et al, 2020;Haghighi et al, 2021). As tools emerge to interrogate individual cell connectivity and merge them with neuronal subtypes defined in other contexts, heterogeneity has been identified within "subclasses" (Campagnola et al, 2021).…”
Section: Bridging Molecular and Functional Characterization Of Areas With Multi-omic Analysesmentioning
confidence: 77%
“…For both, screening additional cell types 44,47,48 and timepoints might increase the ability to detect and characterize perturbations in cell state. If experiments capture both profiling types, the profiles can be integrated and increase their power and resolution 28,29,49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, l-Ergothioneine induced many more transcriptional changes than morphological changes, which influenced genes associated with RNA splicing (GO:0008380) (Figure 4F). This type of analysis opens the door to exploring relationships between particular mRNA levels and specific morphologies when perturbing cells 29,30 .…”
Section: Assessing the Complementarity Of Profiling Morphology And Gene Expression Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the possibility to model their correspondences using computational approaches to translate one data type from the other or to understand their causal relationships. Our dataset has been simultaneously used in a study to identify which gene expression variations correspond with which morphology variations, and vice versa 26 . While this has been explored at the bulk level, our results and previous work based on scRNAseq 18 indicate that this type of analysis could be extended to understand multi-omics connections at the single-cell level.…”
Section: Discussionmentioning
confidence: 99%